PERILAKU SOSIAL IBU DAN ANAK ORANGUTAN (Pongo pygmeus) DI PUSAT REHABILITASI SATWA YAYASAN INTERNATIONAL ANIMAL RESCUE INDONESIA (YIARI) KABUPATEN KETAPANG - Salihin, Salihin; Prayogo, Hari; Nurhaida, Nurhaida (Universitas Tanjungpura, 2020)
Rehabilitation is an effort to restore physical condition or animal behavior, to be returned to natural habitat. The rehabilitation program, with the enrichment of the environment as well as possible with habitat in nature, so that animals are motivated to behave naturally. Orangutan social behavior includes orangutan interactions with other orangutans, orangutans with keepers. The purpose of the research is to examine social behavior, performed by mothers and children of orangutans at YIARI. Observations were made using the Focal Animal Sampling method. The results of the research obtained, the percentage of social behavior of Orangutan Mother, Franky (14.14%) more active than Monti (11.52%) and children of Orangutans, Oso (15.80%), more active than Anggun (12.85%).Keyword: Orangutan, Social Behaviour,YIARI